2010
DOI: 10.1111/j.1439-0418.2010.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and persistence of the entomopathogenic fungus Metarhizium anisopliae in maize fields

Abstract: The entomopathogenic fungus Metarhizium anisopliae (Metsch.) Sorokin (Hypocreales: Clavicipitaceae) was applied in maize fields to control the Western Corn Rootworm Diabrotica virgifera virgifera Le Conte (Coleoptera: Chrysomelidae). Establishment and persistence of two strains of M. anisopliae were investigated after application as ‘fungal colonized barley kernels’ (FCBK) into the soil and as a spore suspension on maize leaves and on the soil surface in 2006 and 2007 at two locations in Hungary. The applied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Our general findings on persistence of the fungus in a row crop field environment are supported by those of Pilz, Enkerli, Wegensteiner, and Keller (2011), who observed survival of M. anisopliae, applied on a barley grain ''Data not available due to sensor malfunction.…”
Section: Discussionsupporting
confidence: 75%
“…Our general findings on persistence of the fungus in a row crop field environment are supported by those of Pilz, Enkerli, Wegensteiner, and Keller (2011), who observed survival of M. anisopliae, applied on a barley grain ''Data not available due to sensor malfunction.…”
Section: Discussionsupporting
confidence: 75%
“…Percent of G. mellonella larvae infected with nematodes was higher for pathogen-treated plots than for control plots (Table 5). Both entomopathogenic nematodes and fungi have been shown to persist in maize Þelds (Kurtz et al 2007, Pilz et al 2011. Entomopathogenic nematodes can persist for several months and up to 2 yr after application to agricultural Þelds (Ferguson et al 1995, Kurtz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Kurtz et al (2007) measured the persistence of several nematode species and found persistence of 2Ð5 mo, and M. anisopliae s.l. was found to persist for at least 15 mo in the soil of maize Þelds (Pilz et al 2011).…”
mentioning
confidence: 99%
“…Thus, initial inoculation rates in our experiment were likely higher than what is found in nature, but persistence was likely lower than that of naturally occurring entomopathogens. In addition, our results highlight the potential for entomopathogenic nematodes and fungi to be applied to Bt maize fields as biological control agents, where a range of concentrations similar to what was used in this study would be appropriate (Krueger & Roberts, 1997;Scheepmaker & Butt, 2010;Toepfer et al, 2010a,b;Pilz et al, 2011).…”
Section: Discussionmentioning
confidence: 62%